Sterility Caused by Floral Organ Degeneration and Abiotic Stresses in Arabidopsis and Cereal Grains - Smith, Ashley R.; Zhao, Dazhong (Frontiers in Plant Science, 2016)
Natural floral organ degeneration or abortion results in unisexual or fully sterile flowers, while abiotic stresses lead to sterility after initiation of floral reproductive organs. Since normal flower development is essential for plant sexual reproduction and crop yield, it is imperative to have a better understanding of plant sterility under regular and stress conditions. Here, we review the functions of ABC genes together with their downstream genes in floral organ degeneration and the formation of unisexual flowers in Arabidopsis and several agriculturally significant cereal grains. We further explore the roles of hormones, including auxin, brassinosteroids, jasmonic acid, gibberellic acid, and ethylene, in floral organ formation and fertility. We show that alterations in genes affecting hormone biosynthesis, hormone transport and perception cause loss of stamens/carpels, abnormal floral organ development, poor pollen production, which consequently result in unisexual flowers and male/female sterility. Moreover, abiotic stresses, such as heat, cold, and drought, commonly affect floral organ development and fertility. Sterility is induced by abiotic stresses mostly in male floral organ development, particularly during meiosis, tapetum development, anthesis, dehiscence, and fertilization. A variety of genes including those involved in heat shock, hormone signaling, cold tolerance, metabolisms of starch and sucrose, meiosis, and tapetum development are essential for plants to maintain normal fertility under abiotic stress conditions. Further elucidation of cellular, biochemical and molecular mechanisms about regulation of fertility will improve yield and quality for many agriculturally valuable crops.